Species Diversity of Aquatic Plants in Kaeng Loeng Chan Reservoir, Maha Sarakham Province - ‪Tokaew, ‪Worachat; Mokhamul, Piya; Phromprasit, Phutsadee (SciTech Research Journal, 2019)
The objective of this research is study on species diversity of aquatic plants in Kaeng Loeng Chan reservoir. The survey was studied between January 2013 and September 2013. Thirty-five of 5x5 m sample plots were distributed throughout the study area, plant specimen collection, photographed and species identification including frequency and relative frequency calculating were done. Results of the research were as follows: Forty-five species of two ferns and 43 flowering plants were found in in Kaeng Loeng Chan reservoir. Five plants namely; Water Hyacinth (Eichhornia crassipes (Hart.) Solms.) Giant Mimosa (Mimosa pigra L.) Water Mimosa (Neptunia oleracea Lour.) Swamp Morning Glory (Ipomoea aquatica Forssk.) และ Creeping Water Primrose (Ludwigia adscendens (L.) Hara) are the most found. The relative frequency value of them are 7.56, 6.91, 6.69, 6.48, and 6.05, respectively, and E. crassipes and M. pigra are invasive alien plants in Thailand.